2022
DOI: 10.3389/fendo.2022.837902
|View full text |Cite
|
Sign up to set email alerts
|

Is Natural Orifice Specimen Extraction Surgery Really Safe in Radical Surgery for Colorectal Cancer?

Abstract: BackgroundThe main feature of natural orifice specimen extraction (NOSE) is its avoidance of an auxiliary abdominal incision. The safety of NOSE remains controversial. This study aimed to investigate the early safety of transanal NOSE in the treatment of sigmoid colon and upper rectal cancer from the follow aspects: clinical and pathological characteristics, inflammatory and immune indicators and postoperative complications.MethodsData from 125 patients diagnosed with sigmoid colon, and upper rectal cancer by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…However, extensive multicenter studies [20][21][22] have shown that preoperative ushing of the bowel with povidone-iodine solution and postoperative abdominal lavage signi cantly reduce the risk of infection. The fact that no complications were observed in the RPLS + NOSE group in our study demonstrates that strict adherence to aseptic technique and pro ciency in retrieving specimens through the natural lumen can be effective in reducing such risks.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive multicenter studies [20][21][22] have shown that preoperative ushing of the bowel with povidone-iodine solution and postoperative abdominal lavage signi cantly reduce the risk of infection. The fact that no complications were observed in the RPLS + NOSE group in our study demonstrates that strict adherence to aseptic technique and pro ciency in retrieving specimens through the natural lumen can be effective in reducing such risks.…”
Section: Discussionmentioning
confidence: 99%
“…T cells can be divided into two subpopulations, CD3 + CD4 + and CD3 + CD8 + T cells, according to different surface antigens, and the balance between them is an important insurance for maintaining normal immune system work, and the ratio of the two is an important indicator to assess immune function [ 6 , 7 ]. In a recent study, CD3 + T lymphocytes and CD4 + /CD8 + ratio levels on the second postoperative day were determined to be higher in patients who underwent laparoscopic-assisted natural orifice specimen extraction than in the conventional laparoscopic-assisted radical resection group, thus confirming the early safety after laparoscopic-assisted natural orifice specimen extraction [ 8 ]; Gang Wang et al showed that fast-track surgery had better protection of patients’ immune function postoperatively compared to laparoscopic surgery, with less impact on CD3 + ,CD4 + T lymphocytes, CD4 + /CD8 + ratio and fewer perioperative complications [ 9 ]. Hence, detecting changes in T-lymphocyte subsets in peripheral blood and using them to assess immune response have aroused the people’s interests.…”
Section: Introductionmentioning
confidence: 91%
“…Currently, the most prevalent approach involves making an auxiliary incision in the abdomen to facilitate the specimen's extraction. Additionally, there is literature supporting the use of Natural Orifice Specimen Extraction Surgery (NOSES) or specimen extraction via the ileostomy site to enhance the surgical outcome (10)(11)(12). In some cases, performing NOSES in patients with larger tumors or thickened intestinal walls and mesentery can be challenging or unsuccessful.…”
Section: Introductionmentioning
confidence: 99%